Tracheal Aspirate Galactomannan Testing in COVID-19-Associated Pulmonary Aspergillosis - Román-Montes, Carla M.; Bojorges-Aguilar, Saúl; Díaz-Lomelí, Paulette; Cervantes-Sánchez, Axel; Rangel-Cordero, Andrea; Martínez-Gamboa, Areli; Sifuentes-Osornio, José; Ponce-de-León, Alfredo; González-Lara, Maria F. (Frontiers in Fungal Biology, 2022)
COVID-19 associated pulmonary aspergillosis (CAPA) is a challenging complication in critically ill patients. The recommended diagnostic method is bronchoalveolar lavage (BAL) culture and galactomannan testing, which were not widely available during the pandemic. There is scarce information regarding galactomannan (GM) testing in other respiratory specimens. Our objective was to compare the agreement of GM between BAL and tracheal aspirate (TA) samples. We selected ICU patients with COVID-19 and suspected CAPA. GM was routinely done in BAL. We performed GM in TA samples and compared the results. Agreement was evaluated with Cohen's Kappa coefficient. GM was considered positive when an OD index ≥1 in BAL and ≥2.0 in TA were found. Probable CAPA was considered when the ECMM/ISHAM criteria were met. Descriptive analysis of clinical characteristics and mortality was made. We included 20 patients with suspected CAPA of which, five (8%) met the probable category. Aspergillus fumigatus was the most frequent isolate. We found moderate agreement between BAL and TA GM (Kappa= 0.47, p=0.01, 95%CI 0.04-0.9), TA GM had 75% sensitivity (95%CI 19.4-99.4%), 81.2% specificity (95%CI 54.4-95.9%), 50% positive predictive value (95%CI 23.8-76.3%) and 92.8% negative predictive value (95%CI 70.1-98.6%), and 80% accuracy (95%CI 56.3- 94.3%). Three (60%) patients with probable CAPA died during hospitalization compared to 40% (6/15) without CAPA (p= 0.4). In conclusion, moderate agreement between TA GM and BAL was found. TA testing may aid ruling out CAPA due to high negative predictive value when bronchoscopies are unavailable.